The Effects on Pricing, Service Quality and Hotel Atmosphere on Customer Satisfaction and Their Implications on Customer Loyalists at A 3 Star Hotel in Bandung - Enos Julvirta (Journal of Research in Business, Economics, and Education, 2021)
Bandung is a popular destination for tourists, especially domestic tourists. In supporting tourist attractions, a qualified hotel industry is needed. In practice, there are problems in the form of low number of repeat guests in Bandung. Referring to the results of preliminary studies conducted and the empirical facts found and relevant previous research results, it is estimated that the researcher estimates that there are four factors that predominantly influence customer loyalty in Three-Star Hotels, namely: price setting, service quality, hotel atmosphere and customer satisfaction. In the calculation, the relationship between (1) quality and pricing, (2) customer satisfaction with hotel atmosphere, (3) customer loyalty to price fixing, (4) service loyalty with customer decisions, (5) hotel atmosphere with price fixing at position which is related and significant. Then there are two variables, namely the relationship between service quality and hotel atmosphere. The research method used in this research is a quantitative method with a correlational approach. Data analysis in the study used a path analysis approach (path analysis). The technique of using data using a questionnaire with the number of respondents of 395 respondents.